2015
DOI: 10.22158/wjssr.v1n2p151
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Student Activism: Barriers, Sharing, and Dialectics

Abstract: The present study was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…These findings align with community psychology given its focus on the interaction between individuals and their broader ecological context (Kelly, 2006; Moane, 2003), as well as prior research that suggests young people get involved with social justice for personal and community reasons (Jones & Brewster, 2017; Snyder & Omoto, 2007). Additionally, consistent with previous research, emerging adults expressed both internal and external motivators and barriers for social action (Christensen & Arczynski, 2014). Participants reported constraints within their personal resources (e.g., time) and knowledge about ways of getting involved.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings align with community psychology given its focus on the interaction between individuals and their broader ecological context (Kelly, 2006; Moane, 2003), as well as prior research that suggests young people get involved with social justice for personal and community reasons (Jones & Brewster, 2017; Snyder & Omoto, 2007). Additionally, consistent with previous research, emerging adults expressed both internal and external motivators and barriers for social action (Christensen & Arczynski, 2014). Participants reported constraints within their personal resources (e.g., time) and knowledge about ways of getting involved.…”
Section: Discussionsupporting
confidence: 88%
“…Further, individuals are more likely to remain involved in action if their personal motivations are fulfilled (Snyder & Omoto, 2007). Lastly, research has indicated that college students’ motivations and barriers are associated with commitment to and interest in social justice engagement (Christensen & Arczynski, 2014; Miller et al, 2009). These studies suggest that research on factors contributing to emerging adults’ social justice engagement is worthwhile to understand how engagement might be developed and sustained.…”
Section: Introductionmentioning
confidence: 99%
“…This work involves processing the influence of identities on mentoring relationships in terms of sociopolitical power and marginalization, and examining how a lack of awareness may emerge from privileged statuses and socialization (Arczynski & Morrow, 2017; Hoover, 2016). Further, mentors are encouraged to reflect on their development as qualitative researchers, feminists, multiculturalists, and activists (Christensen & Arczynski, 2014; Hoover & Morrow, 2016). For example, mentors can reflect and process by journaling individually, by engaging in interpersonal discussions, or by organizing communal events focused on how bias and privilege influence mentoring relationships.…”
Section: Cfm Qualitative Mentoringmentioning
confidence: 99%